ANALYSIS OF INJECTOR LOCATION AND DEFECTS OF PRODUCTS RESULTING IN THE MANUFACTURING OF CAR BUMPERS USING MOLDFLOW SOFTWARE - Sanurya Putri Purbaningrum (International Journal Labs, 2022)
Competition between industries is increasing. Every company is required to develop its products so that it has the ability to compete. PT XYZ is a company engaged in the automotive industry, one of its products is car bumpers. The problem faced by PT XYZ is the high number of product defects that are produced. This study aims to reduce product defects produced at PT XYZ. The research method is using injection molding simulation with moldflow software so that the best injector location is known and is expected to reduce production defects. The simulation results show that the best injector location is at the coordinates (752, 391, 239). The simulation results also show that there is no potential for water trap, weld line, and sinkmark defects that occur. However, the potential for warpage defects still exists. Three potential warpage defects that may occur are high warpage of 29%, medium warpage of 16.6% and low warpage of 5.4%.